O Divino Espírito Santo faz festa em Vila de Abrantes/BA: mito, memória, patrimônio e tradição mista - Machado Júnior, Edmundo Fonseca (2012)
The celebration of the Divine Holy Spirit in Vila de Abrantes/BA every Pentecostal year, explains how, through memory and the practice of such celebration, the community rebuilds and restores its past with artifacts from the present. Through their memories, they bring to surface the characters, rules and markers of its own sociocultural and cosmologic origins. The ethnographic work experienced during the years of 2009 and 2010 was paramount to the understanding of the ways through which the community and the Divine manifest and preserve their reciprocity. The memory of the community then makes us understand how this religiosity, defined as Mixed Tradition, gives and is given meaning in the lives of the ones who practice it, besides that, it has an intrinsic relation with the foundation of Abrantes itself. Still, through the inventory of goods made by the community, which considers them as immaterial heritage of its culture, it was possible to rebuild places and preserve the identities, enabling the understanding of the cognitive values present on the surroundings of the buildings in Vila de Abrantes. Such places and identities would come both to distinguish worlds and world views and to influence the social dynamics of the community.